2002
DOI: 10.1161/01.str.0000017220.78722.d7
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Vitamin C Modifies the Association Between Hypertension and Risk of Stroke

Abstract: Background and Purpose-There are no prospective studies to determine whether plasma vitamin C modifies the risk of stroke among hypertensive and overweight individuals. We sought to examine whether plasma vitamin C modifies the association between overweight and hypertension and the risk of stroke in middle-aged men from eastern Finland. Methods-We conducted a 10.4-year prospective population-based cohort study of 2419 randomly selected middle-aged men (42 to 60 years) with no history of stroke at baseline exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
47
0
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(49 citation statements)
references
References 36 publications
1
47
0
1
Order By: Relevance
“…Vitamin C plasma levels over 0.8 mg dl -1 may help to prevent the development of cardiovascular diseases and cancer. 18,19 Statistical analysis Descriptive statistics (means of subject means) were used for mean plaque and bleeding indices and for probing pocket depths. Between group differences were examined using the MannWhitney U test and longitudinal changes within individual patients were analysed by paired t-test for probing pocket depth and vitamin C levels and by Wilcoxon sign rank test for indices.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin C plasma levels over 0.8 mg dl -1 may help to prevent the development of cardiovascular diseases and cancer. 18,19 Statistical analysis Descriptive statistics (means of subject means) were used for mean plaque and bleeding indices and for probing pocket depths. Between group differences were examined using the MannWhitney U test and longitudinal changes within individual patients were analysed by paired t-test for probing pocket depth and vitamin C levels and by Wilcoxon sign rank test for indices.…”
Section: Discussionmentioning
confidence: 99%
“…High levels have been associated with lower risks of diseases especially cardiovascular diseases (Gale et al, 1995;Khaw & Woodhouse, 1995;Bates et al, 1998;Khaw et al, 2001;Kurl et al, 2002). The differences in lifestyle that this represents may help explain the higher risk of mortality and morbidity observed in individuals of lower socioeconomic status (Bennett, 1996;Smith et al, 1996;Rosvall et al, 2000).…”
mentioning
confidence: 99%
“…Several studies have reported an inverse relation between plasma ascorbic acid and cardiovascular diseases and chronic diseases (Enstrom et al, 1992;Gale et al, 1995;Khaw and Woodhouse, 1995;Bates et al, 1998;Khaw et al, 2001;Kurl et al, 2002), suggesting that ascorbic acid concentration is a good marker of lifestyles that may be conducive to good health. We found a strong socioeconomic gradient in plasma ascorbic acid level across the study population.…”
mentioning
confidence: 99%
“…Epidemiologic studies have confirmed a strong inverse relationship between serum ascorbate levels and blood pressure [61][62][63]. Plasma levels of ascorbate are lower in hypertensive subjects (mean 40 umol/L) compared to normotensive controls (mean 57 umol/L) [ 64 ].…”
Section: An Alternative Hypothesis: the Loss Of Ascorbate And Rise Inmentioning
confidence: 96%
“…Numerous animal models have shown a key role for oxidative stress (present in the circulation, blood vessels, and kidney) in mediating hypertension [ 56 ]. Ascorbate administration also lowers blood pressure in many hypertensive animal models [58][59][60].Epidemiologic studies have confirmed a strong inverse relationship between serum ascorbate levels and blood pressure [61][62][63]. Plasma levels of ascorbate are lower in hypertensive subjects (mean 40 umol/L) compared to normotensive controls (mean 57 umol/L) [ 64 ].…”
mentioning
confidence: 99%